Cohesive resources in journalistic texts: comparative analysis in five publications of the Peruvian newspaper El Comercio - Paz Campuzano, Óscar (2022)
This article identifies and compares the cohesion resources, from Beaugrande & Dressler's theoretical proposal, in five journalistic texts about the death of the terrorist leader of the Shining Path, Abimael Guzmán. The analysis of these linguistic mechanisms (repetition, partial repetition, paraphrase, parallelism, ellipsis, proforma, verb tenses and connections) was applied to a report, a chronicle, an opinion column, an editorial and a news item, texts published in the Peruvian newspaper El Comercio. This study concludes that the use of cohesive mechanisms can be explained, to a certain extent, in the communicative intentionality and style of the journalistic genres.